Biblioteki włoskie – między tradycją a nowoczesnością - Adamiak, Kinga (Biblioteka Uniwersytecka w Poznaniu, 2011)
Przez wieki na terenie dzisiejszej Republiki Włoch powstawały najświetniejsze biblioteki w Europie. Od średniowiecza po renesans prężnie się rozwijały i odgrywały dominującą rolę na Starym Kontynencie. Artykuł przedstawia, jak włoskie biblioteki funkcjonują dziś. Poruszając takie zagadnienia, jak: typy bibliotek we Włoszech i współpraca między nimi, normy prawne, którym podlegają, działalność bibliotek narodowych, stowarzyszenia bibliotekarskie, inicjatywy i projekty wykorzystujące w bibliotekarstwie najnowsze techniki informatyczne, podkreśla słabe i mocne strony bibliotekarstwa włoskiego i przywołuje refleksję: jaka jest rola bibliotek włoskich dziś, kiedy lata ich rozkwitu minęły, i czy są one w stanie sprostać wymaganiom współczesności.

For centuries, lands currently belonging to the Republic of Italy boasted the greatest and the most illustrious libraries in Europe. From the Middle Ages to Renaissance, they developed extensively and were dominant in the Old World. The present article, however, concentrates on modern Italian libraries and provides an extensive review of their functioning today. The following issues are covered in the discussion: types of libraries and their cooperation, legal circumstances, the activity of national libraries, library associations and their initiatives and projects aimed at utilization of state-of-the-art IT infrastructures in librarianship. The article also emphasizes strong and weak points of Italian librarianship and ponders on the following: What is the role of Italian libraries today when they are evidently past their prime times? Can the libraries in question meet the requirements of modern times?
Modern Italian libraries – between tradition and modernity
Keywords: biblioteki; libraries; bibliotekarze; librarians; problemy współczesnych bibliotek; problems of modern libraries; włoskie biblioteki; Italian libraries; współczesne biblioteki włoskie; modern Italian libraries